Determinants of Saving Behavior of Purworejo State High School Students Through Saving Intention - Ichtiar Adhi Fauzi; Rusdarti; Jarot Tri Bowo Santoso (Universitas Negeri Semarang, 2026)
The purpose of this study was to analyze the effect of financial literacy, financial attitudes, socioeconomic parents on saving behavior through saving intentions. The population in this study were all grade XI high school students in Purworejo Regency as many as 2841 students. The number of samples used was 167 students calculated using the slovin formula. The sampling technique used was proportional random sampling. This study used a questionnaire method to collect data. The data analysis method used was descriptive statistical analysis and path analysis. The results of descriptive analysis show that saving behavior is in the very good category, financial literacy is in the high category, financial attitudes are in the good category, saving intentions are in the high category, the socio-economic parents are mostly in the low category. There is a positive influence of financial literacy, financial attitudes, parents' socioeconomics on saving intention. There is a positive influence of financial literacy, financial attitudes, parents' socioeconomics, on saving behavior through saving intentions. There is a positive influence of saving intention on saving behavior. Theoretically, this research enriches our understanding of the factors that influence financial behavior. Practically, these results highlight the importance of comprehensive financial education, which not only focuses on knowledge but also on forming positive attitudes and intentions towards saving. In addition, the role of the family, especially parents, in instilling saving habits from an early age cannot be ignored.